L’assurance et la réassurance, un monde de problèmes : un point de vue européen - Bourthoumieux, Jacques (Assurances, 1984)
At the most recent Rendez-Vous de Septembre, held in Monte Carlo, Mr. Jacques Bourthoumieux, President of the Société Anonyme Française de Réassurance, described the viewpoint of an European towards the situations outlined in the reports of Mr. James J. Meenaghan and Mr. B.J. Brennan. We would have liked to include all of these papers in one edition, with a full description of the debate between Messrs. Meenaghan, Brennan and Bourthoumieux under the chairmanship of Mr. A.L. Preston. Lack of space has forced us to divide this exchange of views between two editions of our magazine.